Penerapan Model Lesson Study untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa di Sekolah Dasar - Ni Wayan Siang Wahyuni (Jayapangus Press, 2019)
The background of this paper is the existence of elementary school learning that tends to be teacher-centered. Teacher-centered learning tends not to make students active in learning, resulting in low learning outcomes. The solution to this problem is a student-centered learning model such as the Lesson Study Model. This paper discusses the understanding of lesson Study models and how they are applied in learning.